The multilateral trading system and human rights : a governance space theory on linkages - Mihir Kanade (Routledge, 2018)
This book contributes an original theory to understanding human rights and international trade. It offers the ‘governance space’ framework for analysing the linkages and normative relationships between the multilateral trading system (MTS) and human rights regimes. Drawing upon key case studies, the author identifies connecting strands as also gaps in linkage issues. He further examines the ‘right to development’ approach to resolve tensions between these two regimes and demonstrates how the approach may be the most appropriate road map to finding sustainable solutions in balancing human rights and equitable free trade in a complex globalised world.